2008
DOI: 10.2147/opth.s2836
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence rates of refractive errors among children, adolescents, and adults in Germany

Abstract: PurposeThe prevalence rates of myopia vary between 5% in Australian Aborigines to 84% in Hong Kong and Taiwan, 30% in Norwegian adults, and 49.5% in Swedish schoolchildren. The aim of this study was to determine the prevalence of refractive errors in German children, adolescents, and adults.MethodsThe parents (aged 24–65 years) and their children (516 subjects aged 2–35 years) were asked to fill out a questionnaire about their refractive error and spectacle use. Emmetropia was defined as refractive status betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
4
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 33 publications
7
45
4
6
Order By: Relevance
“…A refractive error of ≤ −1.50 DS was used to define those ‘likely to be myopic’, with a prevalence of 1.5% in 7‐year‐old white European children. Collectively these findings provide strong evidence that (1) prevalence levels of myopia are markedly higher in older compared to younger British children, in agreement with observations in other European ancestry populations 23–25 , (2) that there are broadly similar levels of myopia in European ancestry children throughout the UK, comparable to levels observed in other white European populations of a similar age 26–28 . However there are differences to children of European ancestry in other parts of the world.…”
Section: Discussionsupporting
confidence: 86%
“…A refractive error of ≤ −1.50 DS was used to define those ‘likely to be myopic’, with a prevalence of 1.5% in 7‐year‐old white European children. Collectively these findings provide strong evidence that (1) prevalence levels of myopia are markedly higher in older compared to younger British children, in agreement with observations in other European ancestry populations 23–25 , (2) that there are broadly similar levels of myopia in European ancestry children throughout the UK, comparable to levels observed in other white European populations of a similar age 26–28 . However there are differences to children of European ancestry in other parts of the world.…”
Section: Discussionsupporting
confidence: 86%
“…Based on our findings, myopia was more common in women, and hyperopia was more common in men. This finding is in contrast with previous studies; although some studies have reported higher rates of myopia in women, most studies show that there are higher prevalence rate of myopia in men and hyperopia in women . Because of intergender differences in biometrics, especially elongated axial length in men, we expected a lower rate of myopia in women than men, but we observed the opposite .…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have found a myopia prevalence of about 40% in adults in Germany 26. This is much lower than what has been reported for Asian populations 27–29.…”
Section: Discussionmentioning
confidence: 65%